MEDICINAL PLANTS OF THE NAMANGAN REGION AND METHODS FOR OBTAINING MEDICINAL PREPARATIONS FROM THEM (Uzbekistan Open Conference, 2025)
The article is devoted to the study of medicinal plants of the Namangan region, their biochemical properties, and practical applications in pharmacology. Modern methods of obtaining medicinal preparations from plant materials are considered, including extraction, maceration, percolation, infusions, and distillation. The significance of these plants for medicine, their biological activity, and the possibilities for rational use of the region’s natural resources are demonstrated.